PENGARUH BERBAGAI DOSIS PERENDAMAN EKSTRAK DAUN CENGKEH TERHADAP DAYA TETAS TELUR IKAN MAS (Cyprinus carpio L.) - Heri Setiawan; Benny Diah Madusari; M Bahrus Syakirin (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
This study aims to determine the effect of immersion clove leaf extract against hatching of fish eggs Mas. The experiment was conducted on January 31 -5 in February 2017, at the Laboratory of Fish Seed (BBI) Sojomerto, District Reban, Batang. The study was conducted based on completely randomized design (CRD) with 5 treatments and 3 replications. Parameters measured were hatchability of eggs of fish Mas Treatments were differences in dose soaking leaf extract Clove on fish eggs Mas, namely A (0 ppt), B (5 ppt), C (7 ppt), D (9 ppt), and E (11 ppt). To determine the effect of treatment on the hatchability of eggs. All data was proceed on analysis of variance. Result showed the highest hatching value reached on immerson clove leaf extract at a dose of 9 ppt, around 98,89%. Respectively, a dose of 7 ppt in the amount of 88,89%, 11 ppt reached up 82,22%, 5 ppt of 61,11% and the lowest value on 0 ppt, which is equal tp 17,78%. Water quality in the range of feasible Ph 6-7, temperature 22-240C, and DO 4.32 -5.7ppm.Keywords: Clove Leaf Extract, carp (Cyprinus carpio L.), hatching rate